Peak shaving strategy through a solar combined cooling and power system in remote hot climate areas. (1st April 2015) - Perdichizzi, A.; Barigozzi, G.; Franchini, G.; Ravelli, S.
Highlights: A solar combined cooling and power (SCCP) system is simulated in island mode. The case study refers to a combined cycle with solar field and absorption chillers. Electrical and cooling demand are matched for typical winter and summer days. The SCCP system has higher efficiency than a conventional pure fossil plant. Another advantage of the SCCP system is the reduction in fossil fuel use. Abstract: An effective combination of district cooling with electric power production in an integrated solar combined cycle is presented and evaluated. A remote area in hot climate is assumed as location to highlight the importance of peak shaving strategy in an isolated or weakly interconnected power system. Two solutions for handling peak power demand are taken into account in the present investigation. On the one hand, the integration of a Concentrated Solar Power system (CSP) with a combined cycle power plant is considered to match peak power demand on the grid. On the other hand, the adoption of a district cooling system where cooling energy is produced by absorption chillers is proposed, instead of mechanical refrigeration, to reduce and flatten the load profile. The case study refers to a combined cycle (CC) based on a 46 MW Siemens SGT-800 gas turbine. The CC plant is integrated with a parabolic trough collectors (PTC) solar field and double-effect steam driven absorption chillers feeding a district cooling network. The solar combined cooling and power (SCCP) system is designed to operate in "island mode" to match both electrical and cooling demand on an hourly basis, on a typical winter and summer day. A modeling procedure is applied to accurately simulate the plant operation, including off-design behavior of all plant components. During the day the solar source has the highest priority, whilst the gas turbine (GT) is operated at part-load to follow the load profile. Electric efficiency and fuel savings for the SCCP plant are computed and compared against the ones resulting from a conventional pure fossil system based on analogous combined cycle and compression refrigeration units. Results show that a SCCP system can significantly reduce fossil fuel consumption in both summer and winter peak hours, while providing higher overall efficiency through the whole day, both in summer and winter.